Substrate dependence of CsK2Sb photo-cathode performance - Guo, L.; Kuriki, M.; Yokota, A.; Urano, M.; Negishi, K. (Progress of theoretical and experimental physics, 2017)
A photo-cathode able to generate a high-performance electron beam with large operability is one of the most important devices in an advanced accelerator. In particular, the $\rm CsK_2Sb$ photo-cathode is of interest because it has high robustness and can be driven by visible light. In this study, we performed cathode evaporation on Si(100), Si(111), and GaAs(100) substrates to evaluate the performance dependence on the substrate material and surface state. For each substrate, the cathode performance on the as-received and cleaned substrates were compared. We found that the cathode performance on the cleaned substrate was superior to that on the as-received substrate for all materials. The cathode performance on the cleaned GaAs(100) and Si(100) substrates were similar, but that on the cleaned Si(111) was significantly much lower. This result gives experimental evidence about the substrate surface direction dependence of $\rm CsK_2Sb$ photo-cathode performance.